Healthy Self-Interest? Health Dependent Preferences for Fairer Health Care - Marcello Antonini; Joan Costa-Font (Institute of Labor Economics (IZA), 2025)
Health status can alter individuals' social preferences, and specifically individuals' preferences regarding fairness in the access to and financing of health care. We draw on a dataset of 73,452 individuals across 22 countries and a novel instrumental variable strategy that exploits variation in health status resulting from cross-country exposure to the national childhood Bacillus Calmette–Guérin (BCG) vaccination schedules. We document causal evidence consistent with the unhealthy self-interest hypothesis, which indicates that better health increases preferences for a fairer health care system. We estimate that a one-unit increase in self-reported health increases support for fair health care access by 11% and the willingness to support fair financing by 8%. Our findings suggest that improving population health, they may give rise to stronger support for interventions to improve equitable health system access and financing.
Keywords: I13; I14; I38; 330; health status; preferences for healthcare financing fairness; willingness to pay; social preferences; BCG vaccine; instrumental variables